2015
DOI: 10.15288/jsad.2015.76.578
|View full text |Cite
|
Sign up to set email alerts
|

Drinking to Cope Motivation as a Prospective Predictor of Negative Affect

Abstract: ABSTRACT. Objective: Consistent with research indicating that drinking to cope (DTC) motivation might exacerbate negative affective states within or immediately proximal to discrete drinking episodes, we examined whether yearly deviations in more global levels of DTC motivation prospectively predicted depressive and anxious affect over several weeks. Method: College students (N = 521, 52% women) completed baseline measures of drinking motives, recent depression and anxiety symptoms, recent alcohol use, and alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
4
15
0
Order By: Relevance
“…This finding was supported by a study conducted in Vietnam which indicated that depression was one of the reasons for alcohol relapse [17]. Similarly, other researchers reported that depression and anxiety symptoms had a significant correlation to drinking with a Pearson's correlation of 0.35 and 0.39 ( p < 0.05) [54].…”
Section: Discussionsupporting
confidence: 56%
“…This finding was supported by a study conducted in Vietnam which indicated that depression was one of the reasons for alcohol relapse [17]. Similarly, other researchers reported that depression and anxiety symptoms had a significant correlation to drinking with a Pearson's correlation of 0.35 and 0.39 ( p < 0.05) [54].…”
Section: Discussionsupporting
confidence: 56%
“…Several previous studies have investigated the hypothesis that coping motives might contribute to prolonged emotion dysregulation by examining associations between trait motives and daily/momentary negative affect during a subsequent EMA period. Two studies found associations between trait coping motives and subsequent negative affect (Armeli et al, 2015; Heggeness et al, 2019), whereas one did not (Gorka et al, 2017).…”
Section: Resultsmentioning
confidence: 95%
“…Here mood was measured once in the evening, and participants may have already started drinking-which could have limited variability in reports of negative mood. Drinking motives may also play an important role in understanding mood (Armeli et al, 2008(Armeli et al, , 2015. Negative mood may be a better predictor of unplanned heavy drinking on days when students report higher drinking-to-cope motives.…”
Section: Discussionmentioning
confidence: 99%